Trabecular bone microstructure analysis on data from a novel twin robotic X-ray device. (April 2023) - Klintström, Eva; Klintström, Benjamin; Spångeus, Anna; Sandborg, Michael; Woisetschläger, Mischa
Background: Bone strength is related to both mineral density (BMD) and the bone microstructure. However, only the assessment of BMD is available in clinical routine care today. Purpose: To analyze and study the correlation of trabecular bone microstructure from the imaging data of a prototype Multitom Rax system, using micro-computed tomography (CT) data as the reference method (Skyscan 1176). Material and Methods: Imaging data from 14 bone samples from the human radius were analyzed regarding six bone structure parameters, i.e. trabecular nodes, separation, spacing, and thickness as well as bone volume (BV/TV) and structural model index (SMI). Results: All six structure parameters showed strong correlations to micro-CT with Spearman correlation coefficients in the range of 0.83–0.93. BV/TV and SMI had a correlation >0.90. Two of the parameters, namely, separation and number, had mean values in the same range as micro-CT. The other four were either over- or underestimated. Conclusion: The strong correlation between micro-CT and the clinical imaging system, indicates the possibility for analyzing bone microstructure with potential to add value in fracture assessment using the studied device in a clinical workflow.